Linking Climate Change, Migration Patterns and Vulnerability: The case of Ndem, Senegal - Margaglio,Giordano; Chesnier,Anna (2019)
Projections estimate that by 2050 hundreds of millions to a billion people will migrate elsewhere due to environmental reasons. The increasing frequency and intensity of natural hazards posed by climate change, as well as the slow-onset degradation of habitats all over the planet, will drive more and more species to migrate towards more habitable and safe environments. While much of the literature in this matter focuses on “push and pull” frameworks disregarding the complexity of reality, more efforts are needed to go beyond unilateral investigations of migration drivers and embrace a holistic approach capable of conducting a multifaceted and overarching analysis of this subject. This thesis aim is the one of exploring the complex nexus characterizing climate change and human mobility, through a contextual vulnerability approach adopted in the study of Ndem, a rural village in the Diourbel region of Senegal. During the fieldwork, a combination of qualitative and quantitative methods was applied in the investigation of community resilience, climate perception and vulnerabilities in the village. Results show that, although a rural exodus severely affected the region due to droughts in the 1970s and 1980s, and climatic conditions exacerbated over the past 50 years, Ndem today represents a point of convergence for migratory patterns all over Senegal. This was possible thanks to the interplay of environmental, economic, social, religious and cultural reasons, which, today, brought Ndem to be an example of successful, community-based autonomous adaptation to climate change.
Keywords: Climate Change; Internal Migration; Vulnerability; Sahel; Culture; Desertification; Drought; Ndem; West Africa